Norma internacional de contabilidad 7 y su relación con los otros estados financieros básicos - Luna Vargas, Mabel Leonor (2016)
This research project is composed of three chapters dealing with the International Accounting Standard 7 and its relationship with other basic financial statements, so a conceptual analysis of the International Accounting Standards and texts legal basis related to held the theme. The chapters are divided according to their content, in which first reference to the problem of study followed by the same justification for what you need to provide theoretical basis related to the topic together is done……